Oral health‐related quality of life changes after placement of immediately loaded single implants in healed alveolar ridges or extraction sockets: a 5‐year prospective follow‐up study. Issue 6 (22nd May 2016) - Raes, Stefanie; Raes, Filiep; Cooper, Lyndon; Giner Tarrida, Luis; Vervaeke, Stijn; Cosyn, Jan; De Bruyn, Hugo
Abstract: Objectives: The impact of single implants on oral health‐related quality of life (OHRQoL) is scarcely investigated, especially when combined with immediate placement and loading in extraction sockets. The aim was to describe prospectively the changes of OHRQoL with single implants placed in the esthetic zone in healed ridges or in extraction sockets after 5 years. Material and Methods: Ninety‐six patients, enrolled at three clinical centers, received 102 single implants placed in a healed ridge ( n = 54 implants/50 patients) or in extraction sockets ( n = 48 implants/46 patients). Implants were immediately provisionalized, and permanent crowns were cemented after 12 weeks. Oral health impact profile questionnaires (OHIP‐14) were completed before surgery, after 1 (provisional crown), 6 (permanent crown), 12 and 60 months, respectively. The overall OHIP‐14 score pertains to seven domains with two items each and was assessed on a Likert scale of 0–4 (0 = never and 4 = very often). The evolution of the total OHIP‐14 score and changes within all OHIP domains over time and between groups were assessed with a linear mixed‐effect model analysis. Results: After 5 years, overall implant survival was 98%. The total OHIP‐14 score for both groups combined decreased from 0.50 at baseline to 0.17 at 6 months ( P < 0.001), indicative of improvement. For both groups, this remained stable up to 5 years ( P = 0.41). However, after 5 years, the total OHIP‐14 score revealed a statistically significantly higher improvement in the healed group compared with the extraction group ( P = 0.027). Conclusion: Missing a single tooth in the maxillary esthetic zone leads to limited OHRQoL problems as reflected by a low overall OHIP score. However, OHRQoL improves less in the extraction group, reflecting that replacing a missing tooth is perceived as more beneficial than replacing a present tooth.